High‐Pressure Synthesis of A2NiO2Ag2Se2 (A=Sr, Ba) with a High‐Spin Ni2+ in Square‐Planar Coordination. (17th December 2018) - Matsumoto, Yuki; Yamamoto, Takafumi; Nakano, Kousuke; Takatsu, Hiroshi; Murakami, Taito; Hongo, Kenta; Maezono, Ryo; Ogino, Hiraku; Song, Dongjoon; Brown, Craig M.; Tassel, Cédric; Kageyama, Hiroshi
Abstract: Square‐planar coordinate Ni 2+ ions in oxides are exclusively limited to a low‐spin state (S=0) owing to extensive crystal field splitting. Layered oxychalcogenides A2 Ni II O2 Ag2 Se2 (A=Sr, Ba) with the S=1 NiO2 square lattice are now reported. The structural analysis revealed that the Ni 2+ ion is under‐bonded by a significant tensile strain from neighboring Ag2 Se2 layers, leading to the reduction in crystal field splitting. Ba2 NiO2 Ag2 Se2 exhibits a G‐type spin order at 130 K, indicating fairly strong in‐plane interactions. The high‐pressure synthesis employed here possibly assists the expansion of NiO2 square lattice by taking the advantage of the difference in compressibility in oxide and selenide layers.